Youth-driven creative placemaking: Strategies in reshaping urban vacant space - Amanda Magdareta Rompas; Agus S. Ekomadyo (ARSNET, 2024)
This paper explores the revitalisation of urban vacant spaces driven by creative and cultural capitals. Such revitalisation reflects a creative placemaking approach and this study aims to investigate architectural strategies used to reshape empty spaces in urban environments in such an approach. The use of a creative placemaking approach provides the possibility of expanding urban renewal methodologies that can capture the dynamic needs and demands of society. The case study used in this research is The Hallway Space Bandung. This research uses qualitative methods with a creative placemaking theoretical framework. Data collection was done by semi-structured interviews and field observations; supported with secondary data collection from social media, online articles, and interview videos. The study found that the vacant space is activated as a youth culture space through engagement with local art communities. Such engagement activates the space through multi-purpose spatial arrangements for creative uses, open-plan spaces for collaborative activities, and utilisation of architectural elements as the platform of art. This paper argues that creative placemaking initiatives enable the appropriation of urban vacant space, establishing new public spaces that are innovative and adaptive to new situations and needs of society.